2021
DOI: 10.1002/cre2.435
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus, Epstein–Barr virus, and Candida albicans co‐infection in oral leukoplakia with different degrees of dysplasia

Abstract: Objectives: To identify human papillomavirus (HPV), Epstein-Barr virus (EBV), and Candida albicans in oral leukoplakia with different degrees of dysplasia.Materials and methods: An observational, cross-sectional, descriptive study was performed using 30 formalin-fixed and paraffin-embedded tissues from patients with clinical suspicion of leukoplakia and confirmed diagnosis of oral dysplasia. Histological analyses were performed by two pathologists (interobserver) and dysplasias were classified as mild, moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…9 In addition, co-infection with HPV, C. albicans, and Epstein Barr virus in tongue leukoplakia was involved in dysplastic change of leukoplakia. 10 These results indicate that co-infection with HPV and candida may increase the risk of developing oral cancers. However, the association of oral HPV16/18 with oral candida has not been fully elucidated in Japanese people.…”
Section: Introductionmentioning
confidence: 86%
“…9 In addition, co-infection with HPV, C. albicans, and Epstein Barr virus in tongue leukoplakia was involved in dysplastic change of leukoplakia. 10 These results indicate that co-infection with HPV and candida may increase the risk of developing oral cancers. However, the association of oral HPV16/18 with oral candida has not been fully elucidated in Japanese people.…”
Section: Introductionmentioning
confidence: 86%
“…[101][102][103] Furthermore, co-infection with HPV and EBV in oral leukoplakia can be associated with severe dysplastic changes. 84 Numerous studies reported the HR-HPVs/EBV co-existence ranging from 27.8% to 100% in HPV-related cervical cancer, and the potential cooperation of EBV as a co-factor in this cancer. 82,83,104 Additionally, a published meta-analysis in 2018 demonstrated that co-infection with HPV increases the risk of cervical cancer in EBV + women up to four-fold.…”
Section: Hpv and Ebv Co-infectionmentioning
confidence: 99%
“…Different reports showed the implication of herpesviruses in increasing the risks of cervical dysplasia 82,83 . Co‐infection of HPV with members of herpesviridae especially HSV and EBV was also reported in different studies 83–85 . Regarding HSV, there are two viral genotypes of HSV‐1 and HSV‐2 that are distinguished by envelope antigenic differences, and cause common oral and genital infections worldwide 80 .…”
Section: Co‐infection Of Hpvs With Other Virusesmentioning
confidence: 99%
See 2 more Smart Citations